The effect of mechanical aspiration of the vertebral body on pulmonary arterial pressure before cement injection in the vertebroplasty procedure. (13th March 2018) - Kochai, Alauddin; Enercan, Meric; Kahraman, Sinan; Ozturk, Cagatay; Hamzaoglu, Azmi
Purpose: The aim of this study is to compare the efficacy of the mechanical aspiration technique just prior to cement application in the standard vertebroplasty (VP). Methods: Forty patients were included in the study. In group A, mechanical aspiration of the cavity was done just before the cement injection and in group B aspiration of vertebral body did not perform, VP was done with the same size cannula, same injection force, same injection speed and same cement viscosity. Pulmonary arterial pressures (PAPs) and bloodd -dimer values were recorded preoperatively, 24 h and 3 days after the procedure. The PAP andd -dimer data were statistically compared with Student's t -test. Results: The mean age was 71 (62–87) in A and 70 (64–88) in B. The augmented level was 6.7 in A and 6.9 in B. Cement leakage was present in four in A and six in B. Acute hypotension was observed immediately after cement injection in one patient in A and four patients in B. The preoperative mean PAP in A was 35mm/Hg and elevated to 48 mm/Hg on the first postoperative day and decreased to 42 mm/Hg on the third postoperative day. The mean PAP in B was 36 mm/Hg preoperatively, 71 mm/Hg on the first day, and 58 mm/Hg on the third day ( p < 0.05). Thed -dimer values revealed a difference between groups, the PAP values significantly changed between before and after the operation in both groups ( p < 0.005). Conclusion: Aspiration of the vertebral body can easily be used to decrease the risk of cement leakage and the migration of fatty particles into the pulmonary circulation.